Educational potential of the artistic expression of visual impairment in the books for children and youth - Iveta Gal-Drzewiecka (Ignatianum University Press, 2018)
Current need of the social integration of people with a handicap, either physical, social, or other, finds significant professional response in a field of pre-school and elementary education. In the accordance with the request of holistic child's personality development (harmonious integration of its cognitive, social-emotional, and perceptual-motoric areas) the education by art seems to be helpful and effective in removing barriers and deepening child's skills to understand and respect the otherness and also as one of the effective ways leading to the social acceptation and inclusion of people with some kind of a handicap. Paper deals with the possibilities of educational use of illustrated books for children and youth, which thematize one of the handicap types - visual impairment. It roots from the assumption of high effectivity of the experiential methods ("through personal experience to understanding") and examines inclusive thinking formation options and attitudes of intact pupils through experiential activities, which use illustrated books thematizing blindness. Solution of the issue comes from the analysis and comparison of the poethological aspects of artistic expression of such handicap in concrete book titles. There are compared artistic-expressive and receptive specifics of various illustrative approaches, particularly their aesthetic-experiential potential - extent of possible sensor, emotional, and cognitive experiences, which offer various modalities of the illustrative rendering of visual impairment to the child's recipient. The same attention is given to their ethical and axiological reflection. In the context of these findings, there are defined paradigmatic differences between the books illustrated in traditional ways and artistically experimental books. Following this, there are outlined alternative models of the didactical application of the issue.